Trans Fatty Acids in Food and Their Influence on Human Health - Sebastjan Filip; Rok Fink; Janez Hribar; Rajko Vidrih (Food Technology and Biotechnology, 2010)
Hydrogenated oils tend to have a higher trans fatty acid (TFA) content than oils that do not contain hydrogenated fats. Prospective epidemiological and case-control studies support a major role of TFAs in the risk of cardiovascular disease. In the partially hydrogenated soybean oil, which is the major source of TFAs worldwide, the main isomer is trans-10 C18:1. In the European countries with the highest TFA intake (the Netherlands and Norway), consumption of partially hydrogenated fish oils was common until the mid-1990s, after which they were omitted from the dietary fat intake. These partially hydrogenated fish oils included a variety of very long-chain TFAs. Recent findings from Asian countries (India and Iran) have indicated a very high intake of TFAs from partially hydrogenated soybean oil (4 % of energy). Thus TFAs appear to be a particular problem in developing countries, where soybean oil is used. In 2003, the United States Food and Drug Administration issued a final ruling that required food manufacturers to list the TFAs in their foods on the nutritional facts label. One way to produce 'zero' levels of TFAs is the trans-esterification reaction between vegetable oils and solid fatty acids, like C8:0, C12:0, C14:0 and C16:0.